Desenvolvimento de IHM para técnicas de metrologia óptica por interferência - Silva, Raphael Muniz Siquara (2020)
The non-destructive testing applied to the study of deformation, strain, profile, and the structural fault has great importance in obtaining information relative to the structure and material properties, being essential for example in production quality control and industrial maintenance area. Optical metrology techniques by interference such as Moiré and Shearography are widely used to obtain such information, mainly due to its field application capacity, being not intrusive, having good precision, visual quality, and real-time exhibition possibility. To obtain the final results of both techniques, a set of sequential steps is necessary, involving the initial procedures of the adequacy of the patterns obtained to the studied physical information recovery. Such steps may require the use of different programs and procedures, which makes the experience difficult if the results are not adequate or if it is necessary to make any alteration in the experimental physical setup, requiring a long time due to the need for calibrations and repetitions of the procedure steps. The objective of this work is the development of a human-machine interface (HMI) that integrates all the experimental steps of the Moiré and Shearography techniques, with the possibility of configuring the steps and visualizing the results in real and static time, in addition to application in the field with the use of machine vision. The real-time application facilitates possible changes in the steps or experimental arrangement, in addition to making it possible to obtain different patterns with different objectives. The results obtained prove the quality, speed, and easy configuration of the experimental steps through the developed HMI.